Outcome of closed tibial diaphyseal fracture managed by intramedullary interlocking nail through suprapatellar approach - Kamruzzaman, M.; Sarker, Manash C.; Hossain, M. Zakir; Hassan, S. M. Mainul; Mahmud, M. Rajib; Kabir, G. M. Alamgir (International Journal of Research in Orthopaedics, 2025)
Background: Tibial fractures are among the most common long-bone injuries, and their subcutaneous location makes management challenging. Intramedullary fixation is the preferred treatment for diaphyseal tibial fractures, though the optimal approach remains debated. The suprapatellar approach is increasingly favored by surgeons. Methods: A prospective observational study was conducted at the National Institute of Traumatology and Orthopedic Rehabilitation (NITOR), Dhaka, from September 2021 to March. Thirty-three patients with closed diaphyseal tibial fractures meeting the selection criteria were treated with intramedullary interlocking nails using a suprapatellar approach and followed up for 12 months. Results: The mean age was 38.3±11.6 years, with 70% male patients. The mean duration from injury to surgery was 13.4±3.3 days. Anterior knee pain occurred in only 5 patients (15.2%). The mean VAS score was 0.5±1.1 (range 0–4). Union time averaged 17.9±3.5 weeks; delayed union occurred in 2 cases (6.1%) and nonunion in 1 case (3%). The mean arc of knee motion was 130.3±8.6 degrees. Functional outcome assessed via Lysholm knee score averaged 93.8±8.9. Outcomes were excellent in 72.7%, good in 18.2%, and fair in 9.1% of patients. Conclusions: Intramedullary nailing using the suprapatellar approach for tibial diaphyseal fractures demonstrates favorable outcomes, including high Lysholm scores, low complication rates, reliable union, improved knee motion, and reduced anterior knee pain.